The interaction between operational flexibility and financial flexibility - BOYABATLI, Onur (Institutional Knowledge at Singapore Management University, 2017)
This paper examines the interaction between operational flexibility and financial flexibility in a multi-product business unit that makes operational decisions based on financial resources provided by its parent company (or headquarters). We capture operational flexibility through investment in flexible technology and financial flexibility through higher availability of financial resources. We consider the flexible-versus-dedicated technology choice and capacity investment decisions of a two-product business unit under demand uncertainty in the presence of budget constraints. The unit operates under a capital budget for financing the capacity investment, and an operating budget, which is uncertain in the capacity investment stage, for financing the production. We investigate how financial flexibility in the capacity investment stage (as captured by the stringency of the capital budget) and financial flexibility in the production stage (as captured by the likelihood of having sufficient operating budget to fully cover the production cost) shape the optimal technology choice. We identify the critical role that the relative capacity intensity (the ratio of unit capacity cost to total unit capacity and production cost) of each technology plays. Our results have implications about how to deploy technologies with different capacity intensity profiles, which are shaped by automation level or plant location choices.